TRENDS IN ACTIVE LEARNING PEDAGOGIES IN BIOLOGY EDUCATION: A SYSTEMATIC DOCUMENTARY CONTENT ANALYSIS OF GLOBAL RESEARCH EVIDENCE - Opeyemi Abdullahi ALABI; Abdulraheem Dare GBIGBADUA; Olufunke. O. KAYODE; Olatunji Yusuf ABDULRAHEEM (Jurnal Saintifik (Multi Science Journal), 2026)
Biology education plays a crucial role in developing scientific literacy, critical thinking, and the ability to understand complex biological systems. In response, active learning pedagogies have increasingly been adopted in biology education to enhance student engagement, improve conceptual mastery, and support deeper learning. The purpose of this study was to examine global trends in active learning pedagogies in biology education through a systematic documentary content analysis of empirical research. Specifically, the study sought to identify dominant active learning strategies, analyse methodological patterns and geographical distribution of studies, examine reported learning outcomes, and map the theoretical frameworks underpinning this body of research. The study employed a systematic documentary content analysis design. The selected studies were analysed using a structured coding framework that combined quantitative frequency analysis with qualitative thematic synthesis. The findings reveal a substantial growth in active learning research in biology education, with inquiry-based learning, problem-based learning, flipped classroom models, cooperative learning, and technology-enhanced instruction emerging as the dominant pedagogical approaches. The analysed studies consistently report improvements in academic achievement, conceptual understanding, student engagement, and learning retention. The analysis also indicates that constructivist, sociocultural, and experiential learning theories form the principal theoretical foundations of these pedagogical approaches. Overall, the study contributes to biology education scholarship by synthesising global empirical evidence on active learning practices, clarifying their theoretical grounding, and providing evidence-based insights that can inform instructional practice, curriculum development, and educational policy aimed at improving biology teaching and learning.